Athlete's Perceptions of a “Quarantine” Training Camp During the COVID-19 Lockdown - Washif, Jad Adrian; Mohd Kassim, Siti Fuzyma Ayu; Lew, Philip Chun Foong; Chong, Christabelle Sheau Miin; James, Carl (Frontiers in Sports and Active Living, 2021)
Globally, COVID-19-related movement restrictions have caused significant disruption to athlete’s training and sporting competitions. ‘Quarantine’ camps are one approach to maintain sport-specific training, whilst minimising the risk of COVID-19 transmission between athletes and society. This cross-sectional study aimed to examine the effects of a ‘quarantine’ training camp on athlete’s routines and wellbeing, performance support, perceived stress and sleep behaviours. A survey was completed at the end of a 30-day ‘quarantine’ camp, by 76 elite athletes (17-46 years), predominantly (~80%) Olympic/Paralympic and/or world championship representatives. Athletes described their experiences in comparison to; pre-lockdown training and/or training during ‘lockdown’ (immediately prior to the ‘quarantine’ camp). Compared to ‘lockdown’, the ‘quarantine’ camp revealed improvements (p<0.05; 0.33 ≤ d ≤ 0.90) in access to sport-specific training (28.6%), recovery facilities (22.2%), nutritional choices (17.5%), mental (12.4%) and emotional (11.4%) health, training motivation (20.0%); and perceived stress (7.4%, p<0.05, d= -0.27). The camp resulted in a lower (p<0.05) sleep duration (-8.5%, d= -0.73), but an improved global sleep behaviour score (-5.6%, d= -0.22). During the camp, the performance support athletes received was not different to pre-lockdown (p>0.05), but there was greater sports massage (20.4%, d= 0.39) and physiotherapy usage (18.1%, d= 0.36) (both p<0.05). The adverse effects of lockdown were restored during the camp. A ‘quarantine’ camp may offer comparable training experiences to pre-lockdown training, without inducing additional perceived stress. Coaches and sporting organisations may consider this approach as part of a virus mitigation strategy, whilst maintaining sport-specific training.